Model of redistribution of political parties supporters - Morhun, Mykola (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
The goal of this research is to create a mathematical model of political parties supporters redistribution. In this work it is done via creating a system of differential equation for the case when society has two political parties and non-partisan citizens. In the second part, the model is generalized for the case of n political parties or groups.